Sulfolane-containing aqueous electrolyte solutions for producing efficient ampere-hour-level zinc metal battery pouch cells - Wang, Yu; Wang, Tairan; Bu, Shuyu; Zhu, Jiaxiong; Wang, Yanbo; Zhang, Rong; Hong, Hu; Zhang, Wenjun; Fan, Jun; Zhi, Chunyi (Nature communications, 2023)
Aqueous zinc metal batteries are appealing candidates for grid energy storage. However, the inadequate electrochemical reversibility of the zinc metal negative electrode inhibits the battery performance at the large-scale cell level. Here, we develop practical ampere-hour-scale aqueous Zn metal battery pouch cells by engineering the electrolyte solution. After identifying the proton reduction as the primary source of H 2 evolution during Zn metal electrodeposition, we design an electrolyte solution containing reverse micelle structures where sulfolane molecules constrain water in nanodomains to hinder proton reduction. Furthermore, we develop and validate an electrochemical testing protocol to comprehensively evaluate the cell’s coulombic efficiency and zinc metal electrode cycle life. Finally, using the reverse micelle electrolyte, we assemble and test a practical ampere-hour Zn||Zn 0.25 V 2 O 5 •nH 2 O multi-layer pouch cell capable of delivering an initial energy density of 70 Wh L −1 (based on the volume of the cell components), capacity retention of about 80% after 390 cycles at 56 mA g −1 cathode and ~25 °C and prolonged cycling for 5 months at 56 mA g −1 cathode and ~25 °C. The negative electrode reversibility limits the lifespan of Zn metal batteries. Here, authors report an aqueous electrolyte with a reverse micelle structure that improves the reversibility of the Zn metal anode enabling the production of an ampere-hour-level pouch cell with five months lifetime.